2007
DOI: 10.1021/ci600473z
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Study of Antimicrobial Activity of Some 3-Nitrocoumarins and Related Compounds

Abstract: A new class of antimicrobial agents, 3-nitrocoumarins and related compounds, has been chosen as a subject of the present study. In order to explore their activity and molecular properties that determine their antimicrobial effects, QSAR models have been proposed. Most of the 64 descriptors used for the development were extracted from semiempirical and density functional theory (DFT) founded calculations. For this study literature data containing results of microbiological activity screening of 33 coumarin deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Several of these compounds, in particular 4‐arylamino‐3‐nitrocoumarin derivatives, showed promising activity in reducing the microbial growth in both fungal and bacterial cells 8, 9. Significant antimicrobial activity of a series of 4‐substituted‐3‐nitrocoumarins was also recently confirmed by a QSAR study 10. Previous research has shown that 4‐amino‐3‐nitrocoumarins, tested for pharmacological activity in mice and rabbits, had neurotropic activity, generally inhibiting spontaneous locomotor activity, decreasing hyperactivity induced by phenamine, and prolonging thiopental sleep 11.…”
Section: Introductionmentioning
confidence: 92%
“…Several of these compounds, in particular 4‐arylamino‐3‐nitrocoumarin derivatives, showed promising activity in reducing the microbial growth in both fungal and bacterial cells 8, 9. Significant antimicrobial activity of a series of 4‐substituted‐3‐nitrocoumarins was also recently confirmed by a QSAR study 10. Previous research has shown that 4‐amino‐3‐nitrocoumarins, tested for pharmacological activity in mice and rabbits, had neurotropic activity, generally inhibiting spontaneous locomotor activity, decreasing hyperactivity induced by phenamine, and prolonging thiopental sleep 11.…”
Section: Introductionmentioning
confidence: 92%
“…In a second study from 2007, Debeljak et al sought to identify novel antibiotic coumarin derivatives (51). A random forest was generated using 64 quantum-mechanical and chemical descriptors calculated for 33 known coumarin-based antibiotics.…”
Section: Decision Trees Applied To Antibiotic Drug Discovery: Ligand-mentioning
confidence: 99%
“…Their function in the plant organism is far from clear, although some authors believe that they have growth regulatory functions, or that they act as fungistatic and bacteriostatic agents. 8 In connection with this, several arylamino-and (heteroarylamino)-3-nitrocoumarin derivatives were synthesized and their antimicrobial activity determined. [5][6][7] Significant antimicrobial activity of a series of 4-aryl-substituted 3-nitrocoumarins was recently demonstrated by Debeljak and co-workers.…”
Section: Introductionmentioning
confidence: 99%